Somatic protein pool, muscle mass and sarcopenia as criteria for nutritional status in pediatrics - M. T. Shakurova; A. Yu. Vashura; T. A. Kovtun; T. N. Sorvacheva (Лечащий Врач)
Background. Nutritional status reflects the relationship between consumption and metabolism of nutrients, in the form of objective parameters of the body, its biological media and components.Results. A review of the literature is presented. To assess nutritional status, available anthropometric parameters that have proven clinical and prognostic significance (body weight, body mass index, etc.) are used. However, these indicators do not fully reflect the component composition of the body, which is critically important for some diseases and conditions. A more informative indicator is the somatic protein pool – the reserve/physiological reserve of amino acids in the body, which provides a pool of skeletal muscle mass. Muscle tissue is the main reserve of amino acids in the body; it becomes a donor of the necessary protein for repair and to meet increased needs in the acute phase of the disease/treatment of patients with hypercatabolism in chronic diseases, injuries, oncopediatrics, etc. An important criterion for assessing nutritional status is the analysis of the risk of sarcopenia. Sarcopenia (decreased muscle mass) and dynapenia (decreased muscle strength) lead to increased risk of disease, mortality, and poor quality of life. Sarcopenia can occur not only in hypercatabolism, but also in obese children, which increases the risks of insulin resistance and metabolic syndrome, while the unfavorable prognosis is greatly enhanced. This indicates the need to use various methods for assessing muscle mass/strength, as well as identifying the risk of developing sarcopenia for adequate differentiated nutritional support and other rehabilitation factors depending on the etiological factors. In the correction of sarcopenia, it is important to take into account its etiopathogenesis. Increasing protein in the daily diet is effective in slowing or preventing muscle catabolism and sarcopenia, including in obese children. However, restoration of skeletal muscle mass and prevention of sarcopenia is not an isolated increase in protein in the diet, but a nutritious diet with a sufficient content of easily digestible protein and the search and possible elimination of the causes of sarcopenia and factors contributing to its aggravation.